Structural, optical and Judd-Ofelt parameters study on samarium and dysprosium ions doped calcium sulfate and magnesium sulfate ultra-phosphate glasses - Aliyu Mohammed Aliyu, 1980- , author; Rosli Hussini, supervisor; Nor Ezzat Ahmad supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Fizik)) - Universiti Teknologi Malaysia, 2019